2019
DOI: 10.3899/jrheum.181460
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Systemic Sclerosis: Results of a Systematic Review and Metaanalysis

Abstract: Objective.Through a systematic literature search (SLR) and metaanalysis, to determine maternal and fetal outcomes in pregnancies involving systemic sclerosis (SSc), to analyze the effect of pregnancy on disease activity, and to examine predictors of fetal and maternal outcomes.Methods.An SLR was performed for articles on SSc and pregnancy published between 1950 and February 1, 2018. Reviewers double-extracted articles to obtain agreement on > 95% of predefined critical outcomes.Results.Out of 461 publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
(50 reference statements)
3
27
0
Order By: Relevance
“…Patients with SSc have a 2.3 times higher chance of cesarean delivery. 18 In this case, vaginal delivery was preferable because there was no vaginal constriction or contractures. We warmed the delivery room and intravenous fluids to prevent any problems related to Raynaud phenomenon during delivery.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Patients with SSc have a 2.3 times higher chance of cesarean delivery. 18 In this case, vaginal delivery was preferable because there was no vaginal constriction or contractures. We warmed the delivery room and intravenous fluids to prevent any problems related to Raynaud phenomenon during delivery.…”
Section: Discussionmentioning
confidence: 88%
“…17 A recent systematic review reported that pregnancies involving SSc had a higher risk of miscarriage, fetuses with IUGR, preterm birth, and newborns with a low birth weight. 18 Additionally, patients with SSc had a 2.8 times higher chance of developing gestational hypertension. As a result, more frequent evaluation of blood pressure, urinalysis, and renal function is required, and management should be provided in a specialized center, with a multidisciplinary team capable of identifying and promptly treating complications.…”
Section: Discussionmentioning
confidence: 99%
“…Women with SSc present higher frequency of adverse events during pregnancy, including miscarriage, intrauterine growth restriction and gestational hypertension. [23]. Reduced levels of EPCs were found in patients affected by SLE [21]; in patients with SLE, pregnancy is considered at high risk, both for the maternal and foetal outcome [24].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is a known feature of some autoimmune connective tissue diseases; altered levels and function of EPCs have been detected in rheumatoid arthritis (RA), systemic sclerosis (SSc) and systemic lupus erythematosus (SLE) [16][17][18][19][20][21]. Interestingly, these conditions are associated with increased risk of adverse obstetric outcome [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…59 Patients with systemic sclerosis who achieve pregnancy have a higher prevalence of adverse pregnancy outcomes (odds ratio [OR]: 1.9 for miscarriage; 3.8 for low birth weight; 2.4 for preterm birth). However, optimisation of disease control prior to conception decreases this risk, 60 although progression of disease during pregnancy was observed in 14.3%. Close monitoring in specialist centres with support from obstetrics, rheumatology, and respiratory can aid in optimising outcomes.…”
Section: Systemic Sclerosismentioning
confidence: 99%